SMS reminders improve re-screening in women and heterosexual men with chlamydia infection at Sydney Sexual Health Centre: a before-and-after study. Issue 1 (19th April 2012) - Guy, Rebecca; Wand, Handan; Knight, Vickie; Kenigsberg, Aurelie; Read, Phillip; McNulty, Anna M
Abstract : Background: In 2009, Sydney Sexual Health Centre implemented a short message service (SMS) reminder system to improve re-screening after chlamydia infection. SMS reminders were sent at 3 months recommending the patient make an appointment for a re-screen. Methods: Using a before-and-after study, the authors compared the proportion re-screened within 1–4 months of chlamydia infection in women and heterosexual men who were sent an SMS in January to December 2009 (intervention period) with a 18-month period before the SMS was introduced (before period). The authors used a χ 2 test and multivariate regression. Visitors and sex workers were excluded. Results: In the intervention period, 141 of 343 (41%) patients were diagnosed with chlamydia and sent the SMS reminder. In the before period, 338 patients were diagnosed as having chlamydia and none received a reminder. The following baseline characteristics were significantly different between those sent the SMS in the intervention period and the before period: new patients (82% vs 72%, p=0.02), aged <25 years (51% vs 33% p<0.01), three or more sexual partners in the last 3 months (31% vs 27%, p<0.01) and anogenital symptoms (52% vs 38%, p<0.01). The proportion re-screened 1–4 months after chlamydia infection was significantly higher in people sent the SMS (30%) than the before period (21%), p=0.04, and after adjusting for baseline differences, the OR was 1.57 (95% CI 1.01 to 2.46). Conclusions: SMS reminders increased re-screening in patients diagnosed as having chlamydia at a sexual health clinic. The clinic now plans to introduce electronic prompts to maximise the uptake of the initiative and consider strategies to further increase re-screening.